Measuring income inequalities beyond Gini index - Eduard Nežinský; Mikuláš Luptáčik (University of Economics in Bratislava, Department of Economic Policy, 2018)
Growing interest in the analysis of interrelationships between income distribution and economic growth has recently stimulated new theoretical as well as empirical research. Since existing theoretical models propose inequality is detrimental to growth, while others point at income inequality as an essential determinant supporting economic growth. Measures such as head-count ratio for poverty index or widely used Gini coefficient are aggregated indicators without deeper insight into income distribution among the poor or the households. To derive an indicator accounting for income distribution among the income groups, we propose output oriented DEA model with inputs equal unit and weights restrictions imposed so as to favour higher income share in lower quantiles. We demonstrate the merit of this approach on the quintile income breakdown data of the European countries. Prioritizing lower income groups welfare, countries –e.g. Slovenia and Slovakia –can be equally favoured by the new proposed indicator while assessed differently by Gini index. Intertemporal analysis reveals a slight deterioration of income distribution over the period of 2007 –2017 in a Rawlsian sense.
Keywords: I31; C61; O15; 330; Income distribution; Rawlsian utility; data envelopment analysis; weights restriction; Malmquist index